2020
DOI: 10.17648/diversitas-journal-v5i3-1193
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade pós-colheita de frutos do umbuzeiro (Spondias tuberosa Arruda) armazenados sob atmosfera modificada

Abstract: O umbu é nativo do semiárido brasileiro. Ele participa como base alimentar e para as populações rurais da região Nordeste, sua exploração umbu é feita de forma extrativista, constituindo uma importante fonte de renda complementar e de mão-de-obra familiar para as comunidades do Semiárido Brasileiro. Com base nos problemas provenientes da rápida maturação e das elevadas perdas, objetivou-se avaliar a qualidade pós-colheita de frutos do umbuzeiro armazenados sob atmosfera modificada e ambiente natural em diferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…The mean total mass of umbu fruits was approximately 21 g, varying from 19.8 to 23.0 g (Table 2), with the fruits from Queimadas being the heaviest. The mean value (MTF) obtained in this study was similar to that found by but higher than that of Santos (1997), who found a mean fruit mass of umbu fruits of 18.4 g. These results were also higher than those obtained by Alves et al (2020) in their study on the postharvest quality of umbu fruits from Santana do Ipanema/ AL, with 15.38 g. The variation found in these studies may be related to the characteristic physiological maturation (late or early) and fruit growth of each genotype, the period between fruit harvest and evaluation, and the edaphoclimatic conditions, such as the annual rainfall rate (as verified in Figure ), soil characteristics, and the local temperature of each location. Despite these mean values, there is no clear standard with regard to the mass of umbu fruits meant for sale.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The mean total mass of umbu fruits was approximately 21 g, varying from 19.8 to 23.0 g (Table 2), with the fruits from Queimadas being the heaviest. The mean value (MTF) obtained in this study was similar to that found by but higher than that of Santos (1997), who found a mean fruit mass of umbu fruits of 18.4 g. These results were also higher than those obtained by Alves et al (2020) in their study on the postharvest quality of umbu fruits from Santana do Ipanema/ AL, with 15.38 g. The variation found in these studies may be related to the characteristic physiological maturation (late or early) and fruit growth of each genotype, the period between fruit harvest and evaluation, and the edaphoclimatic conditions, such as the annual rainfall rate (as verified in Figure ), soil characteristics, and the local temperature of each location. Despite these mean values, there is no clear standard with regard to the mass of umbu fruits meant for sale.…”
Section: Resultssupporting
confidence: 84%
“…Seasonal umbu production occurs in the rainy period, from December to June (ALVES et al, 2020;BATISTA et al, 2015), varying according to the region and rainfall distribution as well as the types of soil and genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Para o DT foi 27,9 mm (PVC), 25,7 mm (controle) e 25,2 mm (fécula) no último dia, observando assim que a redução foi maior que o resultado deMenezes et al (2017) e concordando com a Figura 2 de perda de massa que se mostrou maior.Verificou-se a oscilação mínima do pH referente aos frutos de umbuzeiro nas amostras ao decorrer do armazenamento(Figura 11). Os valores não diferenciaram significativamente, no último dia os tratamentos fécula e PVC chegaram a 2,1 e 2,3 respectivamente Alves et al (2020). estudando o gênero Spondias perceberam valores em uma faixa de 1,88 a 3,05, resultados aproximados foram obtidos com os frutos avaliados no atual estudo.…”
unclassified